α-Glucosidase Inhibitory, Anti-Oxidant, and Anti-Hyperglycemic Effects of -Ham. in STZ-Induced Diabetic Rats - Muhammad Younus; Muhammad Mohtasheem ul Hasan; Khalil Ahmad; Ali Sharif; Hafiz Muhammad Asif; Muhammad Rahil Aslam; Ihsan ul Haq; Zulfiqar Ahmad (SAGE Publishing, 2020)
In this study, we aimed to investigate the antidiabetic effects of Euphorbia nivulia (En) , native to Cholistan Desert area of Bahawalpur, Pakistan. First, we performed high-performance liquid chromatography analysis and found that this plant contains ferulic acid, gallic acid, quercetin, benzoic acid, polyphenols, and flavonoids. Then, we performed in vitro and in vivo studies to assess its effects on diabetic Wistar rat model. The experiments were performed and compared with control drug glibenclamide. The 70% hydroalcoholic extract of En exhibited 97.8% in vitro α-glucosidase inhibitory effect at a dose of 1.0 mg/mL. We orally administered the extract of En and control drug to the streptozotocin (STZ)-induced diabetic rats and analyzed its antidiabetic effects. We found that the extract of En with a dose of 500 mg/kg/body weight exhibited significant effect to reduce blood glucose in STZ-induced rats as compared with the control group ( P < .001). Our histological data also showed that the extract significantly improved the histopathology of pancreas. Collectively, both in vitro and in vivo studies revealed that En possesses α-glucosidase inhibitory, antioxidant, and anti-hyperglycemic effect in STZ-induced diabetic rats.